Highly selective laser-induced graphene (LIG)/polysulfone composite membrane for hydrogen purification. (March 2021) - Mishra, Naveen K.; Patil, Nutan; Anas, Muhammad; Zhao, Xiaofei; Wilhite, Benjamin A.; Green, Micah J.
Abstract: This manuscript reports for the first-time the application of Laser-Induced Graphene (LIG) fabricated on polysulfone as a highly permselective asymmetric membrane for separation of hydrogen and carbon dioxide. Prior work has shown that LIG can be photothermally formed on the surface of a polymeric substrate; this method is rapid and scalable and has previously been applied for aqueous ultrafiltration membranes on polysulfone, polyethersulfone, and polyphenylsulfone substrates. LIG/polysulfone gas separation membranes combine the molecular sieving mechanism of LIG with the solution-diffusion mechanism of polysulfone while enhancing both H2 :CO2 selectivity and H2 permeance. These membranes achieved an H2 :CO2 selectivity of 30.5 ± 1.4 and H2 permeance of 176.4 ± 19.5 GPU (1 GPU = 3.35 × 10 −10  mol m −2  s −1  Pa −1 ). This rapid surface modification of conventional polysulfone membranes with a LIG layer has a potential industrial application for high throughput hydrogen separation. Graphical abstract: Image, graphical abstract